Validation of a New Method for Frequency Domain Dynamic Simulation and Damage Evaluation of Mechanical Components Modelled with Modal Approach. (2015) - Braccesi, Claudio; Cianetti, Filippo; Tomassini, Lorenzo
Abstract: This paper is focused on the validation of a new method, developed by the authors for finite element analysis calculation, to evaluate, in frequency domain, the fatigue damage of mechanical components modeled by modal approach, subjected to variable amplitude loading exerted as random dynamic loads. The authors theoretically demonstrate that the statistical properties ( spectral moments ) of the PSD functions matrix of stress tensor of the model are obtainable with no margin for error only from PSD functions matrix of the modal coordinates and of inputs. A numerical test case is presented to show the capabilities of this new approach.